Combined futsal training: The combination of rotation play training with the HIIT protocol affects anaerobic endurance abilities - As-safa, A. H. T.; Kusuma, I. D. M. A. W.; Syafii, I.; Prianto, D. A.; Triardhana, Y. A.; Pramono, B. A. (Journal of Human Sport & Exercise, 2024)
A training model that combines physicality and tactics is really needed in futsal. This study aims to analyse the effect of rotation play training with HIIT Protocol on the anaerobic abilities of amateur futsal players. This research uses an experimental method with a two-group pre-test and post-test design. The sample in this study consisted of 30 amateur futsal players with an age of 19.23 ± 0.57 years, height of 165.60 ± 5.63 cm, body mass of 59.17 ± 5.24 kg, and BMI of 21.60 ± 1.93. Samples were divided randomly into an experimental group (EG) and a control group (CG). Data analysis used a Paired Sample T-test and an Independent T-test with a significance level of .05 and used Cohen's ES to measure the magnitude of differences between groups. This study used the running anaerobic sprint test (RAST). The variables in RAST that will be analysed are Peak Power (W); Mean Power (W); Peak Power per Weight (W.kg-1); Mean Power per Weight (W.kg-1); Fatigue Index (%); Total effort time (s). The paired sample t-test resulted in a significant difference in EG with significance values of Peak Power p = .010, Mean Power p = .007, Peak Power per Weight p = .011, Mean Power per Weight p = .008, Fatigue Index p = .045, and total effort time p = .011, while in CG all variables do not have significant differences. The Independent T-test found that there was a significant difference between EG and CG with a significance value of p < .05. This research concludes that the rotation play training model with HIIT Protocol has a positive effect on the anaerobic endurance of amateur futsal players